Self-Synchronization Scheme for OTDM Packet Signal Using a Symmetric Mach Zehnder Switch - Ngah, Razali (2005)
The key issue in being able to implement efficient all-optical switching/routing is the ability to carry out synchronization between the switching node and the incoming packets. In this paper we report the simulation results of all optical clock recovery scheme for packet-level self-synchronization using a single symmetric Mach-Zehnder (SMZ) switch. Simulation results demonstrate that clock recovery is successfully carried out employing SMZ switches with high on-off ratio and low crosstalk. On-off ratio for different packets separation has been carried out, showing that long packets separation results in a higher on-off ratio.